Customer service well-being: scale development and validation. Issue 1 (25th January 2020) - Falter, Mareike; Hadwich, Karsten
ABSTRACT: Both researchers and practitioners increasingly recognize well-being of customers as a desirable outcome for business. However, in service science, a scale for measuring well-being in the service context, characterized by customer-employee interaction, has not yet been developed. Thus, the purpose of the present study is to develop a reliable and valid multidimensional scale of customers' perceived well-being through services with customer-employee interactions. This multidimensional scale incorporates the relevant dimensions of how well-being, caused by services, is expressed. Based on a comprehensive interdisciplinary literature review, customer service well-being is conceptualized as a positive response resulting from the experiential, relational, processual and interactive character of service with customer-employee interaction. Following established scale development procedures, the scale comprises five domains: positive emotions, engagement, relationship and meaning & accomplishment, and absence of negative emotions. Thus, customer service well-being as a positive response is affective and cognitive. Two cross-sectorial studies (e.g. healthcare, insurance, retail) are conducted (244 and 833 participants in Germany), which show that the scale is reliable, valid, and distinct but related to other established service measures. Furthermore, customer service well-being affects customers' behavioral intentions and life satisfaction. Directions for further research on customer service well-being and managerial implications are discussed.